Using nudges to promote physical activity and to reduce sedentary behaviour in the workplace: a scoping review protocol - Sarah Forberger; Frauke Wichmann; Chiara Nicoletta Nicoletta Comito (BMJ Open)
Introduction Physical inactivity and sedentary behaviour are associated with numerous health problems and increasing risks of premature morbidity and mortality. Workplace health promotion with a focus on increasing physical activity (PA) and reducing sedentary behaviour is of growing interest. The concept of choice architecture with the use of nudges is a promising approach to influence decision making regarding health behaviours. It can help to understand why people often fail to act in their best interest, to follow well-informed preferences or to achieve their set goals. Nudges, the way the choice is presented, can help to overcome these challenges by using the same habits, biases or boundaries to alter our decision-making in favour of the more preferred behaviour. Aims of the scoping review will be to analyse (a) to what extent the concept of choice architecture is used in workplace health promotion to promote PA and/or to reduce sedentary behaviour and (b) which instruments (nudges) are used to archive that.Methods and analyses Medline, PsychInfo, Web of Science and CINHAL will be searched from 2009 until June 2020. Applying a two-level screening process, title and abstracts will be screened according to a set of predetermined inclusion and exclusion criteria. Included articles will be screened a second time to determine the extent to which choice architecture has been used. Analyses for publication year, location, setting and target group will be provided. Interventions will be analysed presenting the instruments used, number of studies per instrument, combinations of instruments and alteration of the environment. Outcome measures and results will be reported as they occur.Ethics and dissemination Due to the nature of the scoping review, ethical concerns are minimal. No patient data will be included. Results are published in peer-review journals.